Risk Analysis of the Microbial Content In Homeopathic Mother Tincture in Relation to Alcohol Content (Advancements in Homeopathic Research, 2023)
Introduction: Microbial content in homeopathic  mother tincture (MT) is a critical quality parameter. It  is an essential procedure of in-process quality control  (IPQC). However, it requires time and resources. It is  a known fact that a high concentration of alcohol does  not allow microbial growth. Many mother tinctures  are with high alcohol content. But the threshold level  of alcohol content from which it inhibits microbial  growth is not yet known. This study is an attempt to  create a distinct demarcation for grouping the mother  tinctures as high risk and low risk for microbial  growth potential based on the alcohol content (AC).  This will help to apply skip testing to optimize the  resources.Materials & Method: Microbial data of mother  tinctures for 5 years was taken retrospectively for  the analysis and they were grouped into high alcohol  content (HAC, containing more than 50% alcohol)  and low alcohol content (LAC, containing less than  50% alcohol). Mother tinctures with microbial count  below 10,000 were considered as low risk (LR)  and above 10,000 were considered high risk (HR).  The correlation of HAC and LAC with LR & HR  was analyzed in different ratios and the threshold  level of low risk with respect to alcohol content was  identified.Results: There were 2804 batches taken for the data  analysis of which 76.78% batches were of HAC and  23.22% batches were of LAC. Within HAC, 99.95%  of MTs fell under LR. Whereas in LAC, 89.86% fell  under HR. Conclusion: Homeopathic mother tinctures  containing alcohol content more than 50% have low  risk in terms of microbial content. Further, some  mother tinctures, which contain alcohol content less  than 50%, fall under low risk category. Categorizing  mother tinctures based on the risk for microbial  content will help to optimise quality control resources  and to apply the skip testing method.
Keywords: Microbial content in homeopathic mother tincture; alcohol content; microbial contamination; high-risk mother tincture; low-risk mother tincture